The Impact of Airport Construction on Farm Households’ Income - Matufany, Olga Melinda; Istiqomah, Istiqomah; Kadarwati, Nunik; Purnomo, Sodik Dwi (Universitas Muhammadiyah Yogyakarta, 2021)
Infrastructure development is needed to encourage economic growth. However, infrastructure development requires land acquisition, which may adversely impact the community. This study aims to analyze the impact of Kertajati International Airport construction on the farm households’ income and welfare level. This research data used primary data with a simple random sampling method to select 76 farm households in the most affected village. The analysis techniques were income analysis and paired sample t-test. The results showed that farm income was significantly higher before the airport construction. Nevertheless, off-farm income increased after the airport construction, leading to an insignificant household income difference before and after the land acquisition. As for the prosperity level, on average, the farm households lived below the decent living standard. The results imply the importance of increasing farmers’ capacity so that that compensation funds can be utilized to increase household income.